Gaya Hidup Hedonisme, Promosi Penjualan dan Word Of Mouth terhadap Keputusan Pembelian Produk Nevada di Matahari Plaza Simpang Lima Semarang - Akbar Maulana Setiawan; Euis Soliha (IPM2KPE, 2024)
This research aims to explore the influence of a hedonistic lifestyle, sales promotions, and word of mouth on purchasing decisions, with a focus on purchasing Nevada products at Matahari Plaza Simpang Lima Semarang. The research method applied is survey research using a questionnaire distributed to respondents who are consumers of Nevada products. Data analysis was carried out using regression techniques to measure the extent to which independent variables influence purchasing decisions. The research results show that a hedonistic lifestyle, sales promotions, and word of mouth have a positive and significant impact on purchasing decisions for Nevada products at Matahari Plaza Simpang Lima Semarang. The implications of these findings can be used by business people to improve marketing strategies, increase sales promotions, and utilize word of mouth as an effort to strengthen consumer purchasing decisions. In conclusion, this research provides important insights for decision makers in the retail industry regarding the factors that influence consumer purchasing preferences. Keywords: Hedonistic lifestyle, sales promotion, word of mouth